Freedom or isolation?: the impact of discharge from breast cancer follow-up - Hyman-Taylor, Pauline (2012)
The study was conducted following a systematic review of 38 articles (Collins et al 2004), which failed to find strong evidence for the optimum duration and frequency of follow-up, or the personnel best placed to provide it. Against this background of lack of evidence for ongoing follow-up, on the grounds of limited resources and an ever increasing population of breast cancer survivors; the level and nature of service provision for the patients attending a regional breast unit was changed. What was unknown was the impact this may have on the quality of the care and support and future health and well-being. Primary aim: To investigate the experience of being discharged from follow-up breast care services and evaluate the impact of the proposed changes from the patient’s perspective. This thesis reports on interviews with 20 women from the time they were discharged from the service to 2 years post discharge. In addition, 4 participants who developed recurrent disease gave interviews to discuss their experiences. 3 major themes emerged: 1. “Close shave” or “marked woman”? describes the approaches adopted by the women towards their disease, treatment and risk of recurrent disease; 2. A “blessing” or a “curse”? encompasses views of the value of follow-up care; 3. “freedom” or “isolation”? is the account of the impact of discharge from the service on future health, care and well-being. Creating a network of services and working collaboratively with other sectors may well provide the scope and quality of care that women in long-term recovery from breast cancer want and need from the survivorship care of the future.